PERANAN HUKUM DALAM PEMBERDAYAAN CREDIT UNION DI KALIMANTAN BARAT (Studi Pada Credit Union Lantang Tipo) - MICHELL EKO HARDIAN, SH A. 21210083, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
AbstractThis thesis studies raise the issue of " The Role of Law in Empowerment Credit Union In West Kalimantan (Studies in Credit Union Tipo Loud ) " .This study uses Normative Sociological research methods . The survey results revealed that the Credit Union in the Indonesian legal system settings placed as savings and credit cooperatives , but the CU is not the same with ordinary cooperative . Cooperative ordinary still get help from the Government in terms of capital , while CU is independent and does not get help from the Government . At CU savers are members who are owners as well as service users , and members have authority to call it " non-customers " and subject to the Cooperative Act . On the supply side CU can be termed as the equivalent of a cooperative bank services . Also in the CU are taught how to save money in advance ( creating capital ) can only borrow .Constraints faced by the Credit Union Outspoken Tipo in developing its business activities consist of two aspects, namely legal and technical aspects . Juridical constraints faced by CU Outspoken Tipo is related to the government's policy on cooperatives or CU that is still lacking , for example, there is no guarantee the savings of their members in the event of bankruptcy . Technically constraints experienced by the development of the technology used competitor institutions , technology mastery is still lacking , the lack of reliable human resources , and the lack of ready-made with an educational background in the field of cooperatives .Role in empowering local governments in West Kalimantan Credit Union is establish a Regional Credit Guarantee Institutions - PT -shaped enterprises , and the public is expected to not hesitate to put their money in cooperatives and credit unions is growing very rapidly in West Kalimantan . Given the concept of Cooperative CU as an Independent , then the role of the Local Government ( Department of Cooperatives ) not directly , but only through education and training to foster organized by the Department of Cooperatives , issuing permits , legal entity , as well as participation in the National and Regional Level TrainingThe recommendation given is that the need for adequate arrangements in developing business activities Credit Union ; West Kalimantan provincial government needs to encourage and support the development of CU Outspoken Tipo , and the government needs to realize the presence of LPS Credit Unions are regulated by Government Regulation .keywords empowerment and credit union law AbstrakPenelitian Tesis ini mengangkat masalah Peranan Hukum Dalam Pemberdayaan Credit Union Di Kalimantan Barat (Studi Pada Credit Union Lantang Tipo).Penelitian ini menggunakan metode penelitian Normatif Sosiologis. Dari hasil penelitian diketahui bahwa Credit Union dalam sistem hukum Indonesia pengaturannya ditempatkan sebagai koperasi simpan pinjam, padahal antara CU dengan koperasi biasa tidaklah sama. Koperasi biasa masih mendapatkan bantuan dari Pemerintah dari sisi permodalan, sementara CU bersifat mandiri dan tidak mendapatkan bantuan dari Pemerintah. Di CU penabung adalah anggota yang merupakan pemilik sekaligus sebagai pengguna jasa, dan anggota sebagai pemegang otoritas sehingga sebutannya bukan nasabah dan tunduk kepada UU Koperasi. Dari sisi pelayanan CU dapat disebut sebagai koperasi yang pelayanannya setara dengan bank. Selain itu di CU diajarkan cara untuk menabung terlebih dahulu (menciptakan modal) baru bisa meminjam.Kendala yang dihadapi oleh Credit Union Lantang Tipo dalam mengembangkan kegiatan usahanya terdiri dari dua aspek, yaitu aspek yuridis dan aspek teknis. Secara yuridis kendala yang dihadapi oleh CU Lantang Tipo adalah terkait dengan kebijakan pemerintah terhadap Koperasi atau CU yang masih kurang, contohnya tidak adanya jaminan terhadap simpanan anggota ketika terjadi pailit atau bangkrut. Secara teknis kendala yang dialami yaitu perkembangan teknologi yang digunakan lembaga pesaing, penguasaan teknologi masih kurang, kurangnya SDM yang handal, dan kurangnya tenaga siap pakai dengan latar belakang pendidikan di bidang koperasi.Peran pemerintah daerah dalam memberdayakan Credit Union di Kalimantan Barat adalah membentuk sebuah Lembaga Penjaminan Kredit Daerah berbentuk BUMD-PT, dan diharapkan ke depan masyarakat tidak ragu-ragu lagi menempatkan dananya di koperasi maupun credit union yang memang berkembang sangat pesat di Kalimantan Barat. Mengingat konsep CU sebagai Koperasi yang Mandiri, maka peranan Pemerintah Daerah (Dinas Koperasi) secara langsung tidak ada, tetapi hanya sebatas membina melalui pendidikan dan pelatihan yang diselenggarakan oleh Dinas Koperasi, mengeluarkan perizinan, Badan Hukum, serta mengikutsertakan dalam Diklat Tingkat Nasional dan DaerahRekomendasi yang diberikan adalah bahwa perlu adanya pengaturan yang memadai dalam mengembangkan kegiatan usaha Credit Union; Pemerintah ProvinsiKalimantan Barat perlu mendorong dan mendukung perkembangan CU Lantang Tipo; dan pemerintah perlu mewujudkan adanya Lembaga Penjamin Simpanan Koperasi Simpan Pinjam yang diatur dengan Peraturan Pemerintah.kata kunci hukum pemberdayaan dan credit union